Análisis del rendimiento obtenido mediante la labor de cirugía en la inflorescencia del banano - Blacio Borja, Oswaldo Franck (2006)
The present work had as purpose the application from a work of additional field to the realized ones usually in the Banana plantations of the Region, which consists on practicing a “surgery” in the inflorescence of the recently flourished plants of Banana tree, with the purpose that from the moment of having carried out the surgery, the nutriments dedicated to the later formation of the “Acorn” and false hand is distributed in a homogeneous way in the development of the remaining hands, and this way to obtain a fruit of much better quality and at smaller time of crop that fulfills the necessary characteristics to satisfy the international markets. The present practice was carried out among the dates of the July 09 of the year in course to the October 29 of the same year, in the Treasury “ The Marvel ”, located in the Parish Barbones, El Guabo City, County of The Gold. The objectives outlined in the investigation were the following ones: To determine the effect of the surgery in the inflorescence. To evaluate the surgery in the inflorescence with regard to the court grade. To determine the percentage of the quality of the Banana tree, based on the presentation of the fruit. The utilized experimental design was the Completely Randomizado, with 2 treatments and 30 replicas, in those that each replica corresponds to a cluster. After realized the field work and tabulated the obtained data you could conclude the following: The implementation of the surgery of the inflorescence to an early age of the development influenced positively when increasing the weight of the cluster in 4,8% and to reduce the rejection in l9,8% taking like reference the absolute witness. The energy saving in the plant for the future hands eliminated during the pruning, concentrated on the fruit and in the ráquis, this last one presented an increment of 7,80%. The useful yield for cluster was superior with the pruning, being achieved an increment of 9,33%. Other characteristics associated to the quality of the fruit that improved significantly were the size of the fruit evaluated in the second and last hand. The index of bend of the fruit was similar in the fruit of pruned clusters and without pruning. With the pruning it was achieved that 73,3% of the clusters reached the court grade a weeks 11 and 12. The grade or caliber of the fruit in second o'clock and last hand was similar in the treatment surgery and the absolute witness.